(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2012)
Bromination reaction of 2,2,3,6,6-pentamethyl-1,7-dioxaspiro[4,4]no-nen-3-one-8 with molecular bromine and N-bromsuccinimide has been studied. New derivatives of spirolactones have been synthesized on the base of 3-bromomethyl derivative.